Secret science alliance and the copycat crook - Davis, Eleanor, 1983- (New York : Bloomsbury Children's Books, 2010)
Eleven-year-old Julian Calendar thought changing schools would mean leaving his "nerdy" persona behind, but instead he forms an alliance with fellow inventors Greta and Ben and works with them to prevent an adult from using one of their gadgets for nefarious purposes.
Keywords: Inventors -- Fiction; Schools -- Fiction; Clubs -- Fiction; Individuality -- Fiction; Youths' writings; Graphic novels